2019
DOI: 10.1002/vms3.210
|View full text |Cite
|
Sign up to set email alerts
|

Neobalantidium coli: First molecular identification from the Eurasian wild boar, Sus Scrofa in Bushehr Province, Southwestern Iran

Abstract: Balantidium coli is a common parasite of pig and wild boars (Sus scrofa) which can infect humans and several species of mammals. This study aimed to determine the genotype of Balantidium isolated from Eurasian wild boars in Bushehr province, Southwestern Iran. Twenty‐five faecal samples, originating from 25 wild boars captivated in our previous study, were processed. DNA was extracted from the faecal samples and PCR‐amplified, targeting an ITS1–5.8s‐rRNA–ITS2 region of Balantidium genome. PCR product was purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Only a few of the articles retrieved in the literature confirm the presence of B. coli in free-living feral pig feces identified using molecular biology techniques. Similar to this study, B. coli was also identified by means of molecular tools in the feces of free-ranging feral pigs in Iran [59]. Thus, it should be noted that this is the first study conducted in the Americas that identified the zoonotic protozoan B. coli by means of the molecular analysis of a biological sample from free-living S. scrofa, indicating that this bioinvader is a potential reservoir of the protozoan in a tropical region.…”
Section: Discussionsupporting
confidence: 82%
“…Only a few of the articles retrieved in the literature confirm the presence of B. coli in free-living feral pig feces identified using molecular biology techniques. Similar to this study, B. coli was also identified by means of molecular tools in the feces of free-ranging feral pigs in Iran [59]. Thus, it should be noted that this is the first study conducted in the Americas that identified the zoonotic protozoan B. coli by means of the molecular analysis of a biological sample from free-living S. scrofa, indicating that this bioinvader is a potential reservoir of the protozoan in a tropical region.…”
Section: Discussionsupporting
confidence: 82%
“…To illustrate the clonal heterogeneity of MHCC97-L, MHCC97-H and HCC97LM3 cells, an evolutionary tree based on genomic single nucleotide polymorphism (SNP) was constructed in MegaX software. 14 Neighbor-Joining algorithm was used to construct evolutionary tree, and P-distance model was used to calculate distance. Venn diagram was utilized to demonstrate the relationship between mutation sites and gene composition in the three HCC cell lines.…”
Section: Methodsmentioning
confidence: 99%